2010
DOI: 10.1088/0004-637x/715/1/656
|View full text |Cite
|
Sign up to set email alerts
|

The Metal-Enriched Outer Disk of NGC 2915

Abstract: We present optical emission-line spectra for outlying HII regions in the extended neutral gas disk surrounding the blue compact dwarf galaxy NGC 2915. Using a combination of strong-line R23 and direct oxygen abundance measurements, we report a flat, possibly increasing, metallicity gradient out to 1.2 times the Holmberg radius. We find the outer-disk of NGC 2915 to be enriched to a metallicity of 0.4 Z ⊙ . An analysis of the metal yields shows that the outer disk of NGC 2915 is overabundant for its gas fractio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
72
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(80 citation statements)
references
References 56 publications
7
72
1
Order By: Relevance
“…Sánchez interpret this observation as an episode of gas accretion onto the tadpole head. Localized metallicity drops associated with starforming regions have also been observed in other objects, including gamma ray burst host galaxies (Levesque et al 2011;Thöne et al 2014), BCDs (Izotov et al 2009;Werk et al 2010;Sánchez Almeida et al 2014) and dwarf irregular galaxies (Haurberg et al 2013). Variations of metallicity among HII regions located at the same galactrocentric distance are not unusual even in large nearby spirals (Bresolin et al 2012;Li et al 2013); some of these variations could come from localized accretion events.…”
Section: Metallicity Inhomogeneities and Inverted Gradientsmentioning
confidence: 70%
“…Sánchez interpret this observation as an episode of gas accretion onto the tadpole head. Localized metallicity drops associated with starforming regions have also been observed in other objects, including gamma ray burst host galaxies (Levesque et al 2011;Thöne et al 2014), BCDs (Izotov et al 2009;Werk et al 2010;Sánchez Almeida et al 2014) and dwarf irregular galaxies (Haurberg et al 2013). Variations of metallicity among HII regions located at the same galactrocentric distance are not unusual even in large nearby spirals (Bresolin et al 2012;Li et al 2013); some of these variations could come from localized accretion events.…”
Section: Metallicity Inhomogeneities and Inverted Gradientsmentioning
confidence: 70%
“…Recently, Werk et al (2010) have reported a positive gradient in a local galaxy and proposed several scenarios to explain their discovery: (i) a radial redistribution of the metal-rich gas produced in the nucleus; (ii) supernovae blowing out metal-rich gas, enriching the IGM, then falling onto the outer parts of the disk; and (iii) the result of a past interaction.…”
Section: Observed Metallicity Gradientsmentioning
confidence: 99%
“…Werk et al 2010;Rupke et al 2010), during an interaction, metal-poor gas from the outskirts of the galaxy could radially flow towards the center and dilute the metallicity in the inner, high star-forming regions. At the same time, metal-enriched gas could be transported to the outer parts during the interaction, resulting overall in a flattening of the metallicity gradient.…”
Section: Gas Infall Ratesmentioning
confidence: 99%
“…However, they found the metallicity gradients are weak and the merger outskirts have uniform modest abundances (typically around half solar). This is also true for the cases of ELdots in systems that are isolated like NGC 2915 (Werk et al 2010b) which consists of a blue compact dwarf galaxy surrounded by a spectacular H I disk (Meurer et al 1994;.…”
Section: Surveying Outer Disk Star Formationmentioning
confidence: 85%